Low Back Pain and Comorbidity Clusters at 17 Years of Age: A Cross-sectional Examination of Health-Related Quality of Life and Specific Low Back Pain Impacts - Beales, Darren; Smith, Anne; O'Sullivan, Peter; Straker, Leon (Elsevier, 2012)
Purpose: Comorbidities in adults negatively affect the course of low back pain (LBP). Little is known of the presence and/or impact of LBP comorbidities in adolescents. Methods: Subjects from the Raine Study cohort at age 17 years (n = 1,391) provided self-report of diagnosed medical conditions/health complaints, health-related quality of life (36-Item Short Form Health Survey [SF-36]), lifetime experience of LBP, and specific LBP impacts (taking medication, missing school/work, interference with normal/physical activities). Latent class analysis was used to estimate clusters of comorbidities based on diagnosed disorders. Profiles of SF-36 and impact were examined between clusters. Results: Four distinct comorbidity clusters were identified: cluster 1: Low probability of diagnosed LBP or any other medical condition (79.7%); cluster 2: High probability of diagnosed LBP and neck/shoulder pain, but a low probability of other diagnosed health conditions (9.6%); cluster 3: Moderate probability of diagnosed LBP and high probability of diagnosed anxiety and depression (6.9%); cluster 4: Moderate probability of diagnosed LBP and high probability of diagnosed behavioral and attention disorders (3.8%). The clusters had different SF-36 and LBP impact profiles, with clusters 3 and 4 having poorer SF-36 scores, and clusters 2 to 4 having greater risk for specific LBP impacts, than cluster 1. Conclusions: Identified comorbidity clusters support adolescent and adult studies reporting associations between LBP, other pain areas, psychological disorders, and disability. Tracking these clusters into adulthood may provide insight into health care utilization in later life, whereas identification of these individuals early in the life span may help optimize intervention opportunities.